Program Pelatihan Gambar Teknik Menggunakan Aplikasi AutoCAD di SMK Muhammadiyah 3 Samarinda - Binyamin Binyamin; Muhammad Noor Asnan; Bagas Bayu Prasetyo; Daniel Flawijaya Ledau (Pusat Penerbitan Ilmiah Universitas Muhammadiyah Kalimantan Timur, 2020)
Vocational students need some skills that will be used when students finish their studies at school. One of the expected skills is the ability to draw using the AutoCAD program. Where the final ability is expected of the students will be able to create engineering drawings in the form of 2-D models. The purpose of the training program is to develop and improve the technical drawing skills of the XII class students in using the AutoCAD program. Therefore, the students of class XII SMK have the ability to draw machine components and other engineering drawings in 2-D format. The method used in this training program through pre-test instrument, AutoCAD module, discussion, display through slide how to make machine image in 2-D formats and practice how to make the engineering drawing then evaluated with post-test. The result of this program is the improvement of the ability of grade XII students in drawing machine components and other engineering drawings in 2-D format.